Analysis of Indonesia and South Korea's Economic Resilience Strategy - Muhammad Risyad; Stanislaus Riyanta (International Journal of Science and Environment (IJSE), 2026)
In the era of globalization marked by a global growth projection of 2.8% in 2025 amid geopolitical tensions and supply chain disruptions, Indonesia and South Korea face economic shocks affecting GDP, inflation, and unemployment, prompting this qualitative descriptive study to analyze and compare their resilience strategies using secondary documents from BPS, Bank Indonesia, Bank of Korea, and IMF (2023-2025) as population with purposive sampling, analyzed via thematic reduction, comparative tables, and triangulation. Results show Indonesia sustained GDP growth above 5%, unemployment at 4.76%, and inflation at 0.76% in January 2025 through domestic market strengthening, downstreaming, and subsidies, while South Korea addressed 0.1% GDP contraction and high youth unemployment via flexible monetary policies, technological innovation, and vocational training. In conclusion, both nations' adaptive fiscal-monetary synergies proved effective, recommending export diversification for Indonesia and demographic incentives for South Korea to bolster future resilience.